Appreciations of Chilean Teachers on an Education Based on Love: Case Studies - Mujica Johnson, Felipe (2019)
Love as part of the affective dimension of the human being needs to be incorporated significantly into the pedagogical work, however, it is a complex challenge because of the nature of that affect, so this study aims to understand the perspective of the teaching staff. The purpose of the study is to identify the social representation of love in school education by teachers who work in public education. The study responds to the qualitative approach and its participants are six teachers from different pedagogical disciplines. The data collection was done through qualitative reports and semi-structured interviews. The data were subjected to a content analysis consisting of three phases, using the Atlas.ti 7.5 program. The results present two families, semantics of love and the role of love in school education, which are composed of three codes each. It is concluded that teachers perceive love as an essential component for wellbeing and learning, which is socially constructed and transmitted through language, transforming the educational reality.